Which surgical patients benefit from perioperative beta‐blockers?. Issue 11 (November 2015) - Forsea, Monique; Narciso, Philipp
Abstract : Evidence‐Based Answer : In patients undergoing cardiac or vascular surgery or patients with cardiac risk factors undergoing nonvascular surgery, perioperative beta‐blockers reduce 30‐day risk of acute myocardial infarction (NNT=57) and 1‐year mortality (NNT=28), but do not change 30‐day mortality. This benefit is partially offset by increased risk of stroke (NNH=177) (SOR: A, meta‐analysis of RCTs). Patients with 2 or more Revised Cardiac Risk Index (RCRI) factors taking beta‐blockers have a lower 30‐day mortality than patients not taking beta‐blockers undergoing vascular or nonvascular surgery (SOR: B, single cohort study).